Understanding the Complexities: Exploring Secondary School Contextual Challenges Teachers Face in Addressing Indiscipline - Motsekiso Calvin Letuma (Indonesia Approach Education, 2024)
Indiscipline is a cause for worry in schools as it obstructs fulfilling its intended mission of delivering high-quality education. In the face of rampant indiscipline, teachers must possess the aptitude to proficiently manage all the challenges that arise from school disciplinary matters. This research explored teachers’ challenges while dealing with disciplinary matters in schools. The study employed an interpretative paradigm and a qualitative approach with a case study design. The data was obtained through semi-structured interviews with six school management team members and a focus group interview with seven teachers from four specifically selected quintile three secondary schools. The findings indicated limited leadership capabilities from the school leaders, as evidenced by problems such as ineffective establishment of disciplinary committees, insufficient facilities, inadequate communication between parents and the school, young and inexperienced teachers’ challenges, and teacher resistance. The study suggests that continuous training for school leaders is necessary to enhance their ability to inspire admiration and trust among teachers, cultivate a sense of purpose, encourage innovative problem-solving, and foster their and others’ professional development in managing school disciplinary issues. The study introduced a paradigm shift in the design and provision of professional development for schools, expanding beyond curriculum implementation to include disciplinary matters in schools.